2013
DOI: 10.1371/journal.pone.0053661
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 (PTX3) Is Associated with Severe Sepsis and Fatal Disease in Emergency Room Patients with Suspected Infection: A Prospective Cohort Study

Abstract: BackgroundEarly diagnostic and prognostic stratification of patients with suspected infection is a difficult clinical challenge. We studied plasma pentraxin 3 (PTX3) upon admission to the emergency department in patients with suspected infection.MethodsThe study comprised 537 emergency room patients with suspected infection: 59 with no systemic inflammatory response syndrome (SIRS) and without bacterial infection (group 1), 67 with bacterial infection without SIRS (group 2), 54 with SIRS without bacterial infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 42 publications
8
71
4
1
Order By: Relevance
“…However, data presented here suggest that this may not be the case, but rather, elevated PTX3 production induced by select A. baumannii strains appears to correspond with increased susceptibility of mice to infection. Furthermore, in agreement with previously published patient case study data, prolonged elevation of PTX3 levels was associated with development of hypercoagulopathy and DIC in challenged animals (29)(30)(31)(32)(33)(34)(35).…”
Section: Figsupporting
confidence: 91%
See 2 more Smart Citations
“…However, data presented here suggest that this may not be the case, but rather, elevated PTX3 production induced by select A. baumannii strains appears to correspond with increased susceptibility of mice to infection. Furthermore, in agreement with previously published patient case study data, prolonged elevation of PTX3 levels was associated with development of hypercoagulopathy and DIC in challenged animals (29)(30)(31)(32)(33)(34)(35).…”
Section: Figsupporting
confidence: 91%
“…3A). Thus, significant elevation in PTX3 production appeared to be associated with increased disease severity, consistent with published case studies (29)(30)(31)(32)(33)(34)(35).…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…Pentraxin 3 levels also become elevated in subjects with ARDS within 24 h of diagnosis, presumably as an activator of the local innate immune system in the lung (3). In addition, elevated levels of serum pentraxin 3 have been detected in subjects with sepsis and appear to be an important biomarker of sepsis severity (69). Given the strong association of the IL-6 pathway with these conditions, our data suggest that IL-6 trans-signaling could play an important role in elevating these markers of lung disease.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies have shown that PTX3 can be used as a marker for disease severity and fatal outcome in cardiovascular, inflammatory and infectious diseases [16][17][18][19][20][21]. Thus, we developed a novel assay for measurement of PTX3 in body fluids and examined the serum levels from patients with SIRS and sepsis admitted to an ICU as well as controls in order to review the validity of PTX3 as a biomarker in ICU patients.…”
Section: Introductionmentioning
confidence: 99%